Climatic Crop Growth Index in Drought Studies for Land Resources Planning - Das, D.C. (Journal of Soil and Water Conservation, 2022)
After reviewing various definitions as well as classifications of drought events, the Climatic Crop Growth Index (CCGI), for its ability to incorporate the actual plant-soil-climate interaction representing varying crop tolerance to shifting water stress conditions, has been used in this paper to define and classify the droughts. The country has been delineated into four categories of droughts, using data from 94 stations representing different meteorological sub-divisions of India. About 80 per cent area of the country is observed to be prone to droughts. While wily 6 per cent of the geographical area is subject to disastrous droughts, 36 per cent is affected by severe droughts, 14 per eent by large. droughts and 24 per cent by moderate droughts. The areas affected by droughts include many pockets which are not normally suspected to be drought affected areas, when only rainfall and other climatic parameters are considered without consideration of plant growth responses vis-a-vis soil moisture storage limits or soil suctions. The approach also offers the feasibility of comparing alternatives and also providing contingent plans particularly relating to mid season corrections. Annual delineations do not offer full picture of seasonal variations and long dry-spells during the rainy seasons. For developing local land use plans monthly delineations would thus be desirable. Again time series of climatic crop growth indices for the year as well as months and seasons for a given location should be analysed for detecting the variabilities of Index. This would also help in developing appropriate measures to minimise risk or achieve stability in land management system. Since severity of the drought is not only due to lack of availability of moisture but its persistence and succession, feasibility of using moving average series should be further explored to incorporate these effects. The limitations of the approach is in its inadequacy to consider actual soil moisture storages and their variations with induced land management systems and also predicting onset, persistence and succession of drought of a given magnitude.